1992
DOI: 10.1136/hrt.68.12.596
|View full text |Cite
|
Sign up to set email alerts
|

Different distribution of abnormal endocardial electrograms within the right atrium in patients with sick sinus syndrome

Abstract: Background-Prolonged and fractionated right atrial endocardial electrograms are characteristic of paroxysmal atrial fibrillation (idiopathic or associated with sick sinus syndrome). The distribution of these abnormal atrial electrograms within the right atrium and the way it is related to the likelihood that patients with sick sinus syndrome will develop paroxysmal atrial fibrillation was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
3

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 33 publications
2
42
1
3
Order By: Relevance
“…Therefore, abnormal electrograms indicate areas of altered anatomy and conduction that are suitable substrates for reentrant arrhythmias. 5 Since abnormal atrial electrograms increase with advancing age, these electrophysiologic changes may account for the ease with which AF can develop in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, abnormal electrograms indicate areas of altered anatomy and conduction that are suitable substrates for reentrant arrhythmias. 5 Since abnormal atrial electrograms increase with advancing age, these electrophysiologic changes may account for the ease with which AF can develop in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] It was strongly suggested that muscle loss and increase of fibrosis in the atria is a slow but continuous process starting at about 60 years of age. 3 Since aging has a profound effect on structural changes of the atrial muscle, and since fractionated atrial endocardial electrograms may reflect nonsynchronized, delayed local electrical activity through a diseased atrial muscle, 5 it seems reasonable to assume that there may be detectable age-induced changes in atrial endocardial electrograms in patients with paroxysmal atrial fibrillation (PAF). To the best of our knowl-edge, this is the first study designed to clarify the influence of advancing age on atrial endocardial electrograms recorded during sinus rhythm by means of intra-atrial catheter mapping in patients with PAF.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with diseased atrial tissue with progressive fibrodegenerative changes may develop abnormal electrophysiological alterations [7][8][9][10][11]. Connective tissue surrounding atrial myocardial cells represents sites where electrical coupling between adjacent cells is altered [1][2][3].…”
Section: Editorialmentioning
confidence: 99%
“…7 Since not all patients with atrial arrhythmias initiate AF, a substrate for atrial propensity to AF is required for AF initiation and maintenance. [8][9][10] Abnormal responses of the atrium can be elicited by programmed atrial stimulation, such as repetitive atrial firing, fragmented atrial activity, and intraatrial conduction delay, and have been more frequently observed in patients with nonidiopathic PAF. Shorter atrial effective refractory period has been also shown to be of electrophysiological significance in the genesis of AF.…”
Section: Introductionmentioning
confidence: 99%